PREVENTION OF INTERNET ADDICTION IN SCHOOL ENVIRONMENT - Halkovicova, Katarina (IJRDO- Journal of Educational Research, 2017)
The submitted thesis deals with prevention of Internet addiction among pupils at secondaryschool. The aim of this work is to draw attention to this socio-pathological phenomenon and tocontribute to its prevention. It discusses the issue of excessive use of the Internet and socialnetworks, Internet dependence and Internet traps. The thesis has theoretical and practicalcharacter. The first part deals with theoretical knowledge, definitions, risk factors andconsequences of this phenomenon, as well as with the possibilities of prevention. The thesis alsocontains a survey of pupils focusing on their relationship to the Internet and social networks.From our findings, we have subsequently established recommendations for practice.